OP0179 Angiogenesis and blood vessel stability in giant cell arteritis. (23rd January 2014) - Molloy, D.; McCormick, J.; Connolly, M.; Haroon, M.; Veale, D.J.; Fearon, U.; Molloy, E.
Abstract : Background: Giant Cell Arteritis (GCA) is the most common form of primary vasculitis. The pathogenesis is incompletely understood, but involves neoangiogenesis and inflammatory infiltration of the arterial wall. The aim of the present study was to assess blood vessel stability and oxidative damage in patients with the condition and correlate with disease activity. Methods: 20 patients with a clinical diagnosis of GCA were included, 16 of whom had a positive temporal artery biopsy. Temporal artery (TA) sections were assessed for blood vessel maturity (%BVM) by dual-immunofluorescent staining for Factor VIII/αSMA. Oxidative DNA damage (8-oxo-7, 8-dihydro-2'-deoxyguanosine; 8-oxo-dG), lipid peroxidation (4-hydroxy-2-nonenal; 4-HNE), angiogenic growth factor Angiopoietin 2 (Ang2) and it receptor Tie-2 were assessed by immunohistochemistry. Ex vivo TA explant cultures were established directly from fresh biopsy specimens (n=4) and spontaneous release of pro-angiogenic factors were examined by ELISA and gelatin zymography. Patient were categorised into low disease activity (CRP<50 mg/dL vs high disease activity (CRP>50 mg/dL) Results: Strong expression of 8-oxo-dG, 4HNE, Ang2 and Tie2 were demonstrated in the adventitial and intimal regions. 8-oxo-dG and 4HNE correlated with disease activity marker ESR (r=.568, p<0.017: r=.451, p<0.05 respectively). Expression of 8-oxodG significantly correlated with Tie2 (r=0.538, p<0.017) while expression of 4HNE significantly correlated with Ang2 (r=0.0529, p<0.02). A mixture of immature and mature blood vessels was demonstrated in all GCA patients, with a lower number of vessels expressing α-SMA in patients with high disease activity (41% ± 13.4) compared to low disease activity (66% ± 8.2) suggesting a more unstable vascular microenvironment is associated with high disease activity. This was further supported when we demonstrated spontaneous release of pro-inflammatory mediators Ang2, MMP-2, MMP-9, IL-6 and IL-8 from ex vivo TA explants in culture. Furthermore conditioned media from TA explants significantly induced angiogenic tube formation (p<0.05). Conclusions: This is the first study directly demonstrating that vessels in the inflamed temporal arteries from patient with GCA are unstable and are associated with incomplete EC/pericyte interactions, expression of Ang2 and oxidative damage markers. Disclosure of Interest: D. Molloy: None Declared, J. McCormick: None Declared, M. Connolly: None Declared, M. Haroon: None Declared, D. Veale Grant/Research support from: Wyeth, GSK, Abbott, Opsona, Consultant for: Wyeth, GSK, Abbott, Pfizer, Schering Plough, Centocor, Speakers Bureau: Wyeth, GSK, Abbott, Pfizer, Schering Plough, Centocor, Mundipharma, U. Fearon: None Declared, E. Molloy: None Declared